Comparison of efficacy and safety of adjuvant therapies versus sorafenib in hepatocellular carcinoma: a systematic review and network meta-analysis - Quan, Wenjun; Fazlin Zulkifli, Hanifah; Saari, Norhafizah; Shueb, Rafidah Hanim; Mustaffa, Nazri (Frontiers in Pharmacology, 2025)
PurposeDiverse novel therapeutic options for hepatocellular carcinoma (HCC) have surfaced in recent years. However, it is increasingly difficult to select the optimal medication. This research aims to assess overall survival (OS), progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR), adverse events (AEs), and severe adverse events (SAEs) in HCC patients receiving adjuvant therapies compared to those receiving sorafenib.MethodsFour databases were used to search articles. Only randomized controlled trials were included. Indicators such as OS, PFS, DCR, ORR, AEs and SAEs were used as outcomes. The protocol for this meta-analysis was registered with PROSPERO (Registration ID: CRD42024544394).ResultsForty trials were included in this meta-analysis. The Oxaliplatin, Fluorouracil, and Leucovorin (OFL) + sorafenib group and the sintilimab + bevacizumab biosimilar group decreased the risk of death and increased PFS, ORR, and DCR. Yet, they also yielded remarkable adverse effects and severe adverse effects. To sum up, the atezolizumab + bevacizumab combination and tepotinib were recommended due to their favorable performance on all indexes.ConclusionThis study further substantiates the efficacy of combination therapies in HCC, while they cause more toxicity in general. It is pressingly urgent to develop new drugs for liver cancer and find rational strategies to alleviate AEs.Systematic Review RegistrationPROSPERO, identifier CRD42024544394.